UPAYA PENINGKATAN PENGETAHUAN REMAJA MENGENAI PERILAKU SEKS BEBAS DI SMAN 25 BATAM - Fitriani; Andolina, Nuari (LPPM Universitas Awal Bros, 2022)
Sexual behavior is any behavior that is driven by sexual desire either with the opposite sex or with the same sex. Based on some research data shows that the free sex behavior of adolescents in Indonesia is quite worrying. The results of a survey conducted by the 2012 IDHS (Indonesian Demographic and Health Survey) (in Anniswah, 2016) regarding adolescent sexual behavior activities are holding hands 79.6% in men and 71.6% in women, kissing lips 48.1% in men and 29.3% in women, touching/stimulating 29.5% in men and 6.2% in women, intercourse/intercouse 8.3% in men and 0.9% in women. This community service activity is in the form of providing health education through counseling youth about free sex behavior. The results obtained from this community activity before the counseling was carried out, the majority of participants' knowledge was in the sufficient category, namely 37%, participants with less knowledge were 42% and only 17% of participants had good knowledge about free sex behavior. Health education about free sex was carried out with the help of leaflet media, during the activity the participants seemed interested in listening to the counseling given. The results of the evaluation showed that participants understood the material presented, this showed an increase in participants' knowledge about free sex behavior that was conveyed.